Northward Expansion and Intensification of Phytoplankton Growth During the Early Ice‐Free Season in Arctic. Issue 19 (15th October 2018) - Renaut, S.; Devred, E.; Babin, M.
Abstract: In the last decades, reduction of the ice cover has been documented to affect the structure and the functioning of Arctic marine ecosystems. One direct consequence is earlier phytoplankton spring blooms and larger annual primary production compared with previous decades. However, the impact of changes in the dynamics of sea ice specifically on phytoplankton spring blooms, a major contributor of the annual primary production in the Arctic Ocean, remains poorly known. Here we report on their temporal and spatial variabilities in open waters between 2003 and 2013 using satellite ocean color data. We observed a significant increase in primary productivity of phytoplankton spring blooms in different sectors of the Arctic Ocean, especially in the Barents and Kara Seas. Satellite observations also revealed a northward expansion of these blooms at a rate of 1° per decade driven by the Barents and the Kara regions. Plain Language Summary: The declining of the ice cover in the Arctic Ocean has a strong impact on the dynamics of the marine ecosystem. The phytoplankton spring bloom, which can contribute to more than half of the annual primary production in open waters in some regions of the Arctic Ocean and which is tightly linked to the ice cover, is undergoing drastic changes. This key feature represents also a significant food source for higher trophic levels. Our study reveals rapid changes in the magnitude of primary productivity and the spatial distribution of these blooms. We observed a significant increase in primary productivity of phytoplankton spring blooms in different areas of the Arctic Ocean. A northward expansion of these blooms was also observed. Their occurrence at very high latitudes in the central basin, where they were nonexistent and where a low productivity usually prevails, is also a significant finding. Key Points: We report on the temporal and spatial variability of phytoplankton spring blooms between 2003 and 2013 in the Arctic Ocean Primary productivity of phytoplankton spring blooms is increasing in several areas of the Arctic Ocean between 2003 and 2013 Satellite observations revealed a northward expansion of these blooms at a rate of 1° per decade